Into the forest eaudiobook - Hegland, Jean (Recorded Books Inc., 2015)
At first, Into the Forest was a word-of-mouth favorite of booksellers. Soon, larger publishing houses were noticing Jean Hegland's debut novel and giving it rave reviews. Powerful and disturbing, Into the Forest offers images of an all-too-believable future. As America collapses in the chaos of war, pollution, and bankruptcy, two sisters pool their resources to survive alone in the hills above San Francisco. Although dwindling food and increasing isolation threaten them, they soon find a more immediate danger standing at their door. When a young man arrives, his friendship offers tantalizing fulfillment, but his love threatens to divide the sisters. Hegland's provocative work is reminiscent of George Orwell's 1984 and Margaret Atwood's The Handmaid's Tale. It infuses a tale of survival with startling insights into a young woman's quest for strength.